Long-term culture of patient-derived cardiac organoids recapitulated Duchenne muscular dystrophy cardiomyopathy and disease progression - Marini, Vittoria; Marino, Fabiola; Aliberti, Flaminia; Giarratana, Nefele; Pozzo, Enrico; Duelen, Robin; Cortés Calabuig, Álvaro; La Rovere, Rita; Vervliet, Tim; Torella, Daniele; Bultynck, Geert; Sampaolesi, Maurilio; et al. (Frontiers in Cell and Developmental Biology, 2022)
Duchenne Muscular Dystrophy (DMD) is an X-linked neuromuscular disease which to-date incurable. The major cause of death is dilated cardiomyopathy, however the pathogenesis is unclear as existing cellular and animal models do not fully recapitulate the human disease phenotypes. In this study, we generated cardiac organoids from patient-derived pluripotent stem cells (DMD-CO) and isogenic-corrected controls (DMD-Iso-CO) and studied if DMD-related cardiomyopathy and disease progression occur in the organoids upon long-term culture (up to 93 days). Histological analysis showed that DMD-CO lacks initial proliferative capacity, displayed a progressive loss of α-sarcoglycan localization and high stress in endoplasmic reticulum. Additionally, the cardiomyocyte deteriorated over time, and fibrosis and adipogenesis were observed in DMD-CO. RNA sequencing analysis confirmed a distinct transcriptomic profile in DMD-CO which were associated with functional enrichment in hypertrophy/dilated cardiomyopathy, arrhythmia, adipogenesis and fibrosis pathways. Moreover, five miRNAs were identified to be crucial in this dysregulated gene network. In conclusion, we generated patient-derived cardiac organoid model that displayed DMD-related cardiomyopathy and disease progression phenotypes in long-term culture. We envision the feasibility to develop a more complex, realistic and reliable in vitro 3D human cardiac-mimics to study DMD-related cardiomyopathies.